Performance numerical evaluation of modified single-ended primary-inductor converter for photovoltaic systems - Tole Sutikno; Rizky Ajie Aprilianto; Nik Rumzi Nik Idris; Ahmad Saudi Samosir (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Single-ended primary-inductor converter (SEPIC) was considered a good alternative to a DC-DC converter for photovoltaic (PV) systems. The SEPIC converter can operate with an input voltage greater or less than the regulated output voltage, or as a step-up or step-down. As a step-up converter, SEPIC boosts PV voltage to specific levels. However, gain limitation and voltage stress continue to reduce the efficiency of conventional SEPIC converters. Because of this, researchers created a modified SEPIC converter to improve performance. In this paper, six modified SEPIC converters were compared and evaluated. To compare fairly, all modified SEPIC converters are non-isolated and use a single switch. Power simulator (PSIM) software was used to simulate each converter with a BISOL BMO-250 PV module and maximum power point tracking (MPPT) P&O controller. The converter with the highest static voltage gain and lowest duty cycle has been identified. It results in up to ten times voltage increment with a 0.8-duty ratio. All topologies have the same voltage stress, with maximum and minimum values of 30.1 and 29.5 V, respectively. On the other hand, each topology produces different average efficiencies, with the highest and lowest efficiency at 99.5% and 97.2%, respectively.